National union catalog - Library of Congress. Catalog Publication Division (New York : Rowman and Littlefield, 1963)
Includes entries for maps and atlases.
First quinquennial cumulation covers 1958-62; the entries for 1956-57 were combined with the 1953-55 annual vols. of the Library of Congress catalog ... --Books: authors in a cumulation published in 1958 by J. W. Edwards, Ann Arbor, Mich.
Monthly, quarterly, and annual vols. published by the Library of Congress; 1958-62 cumulation published by Rowman and Littlefield, New York; 1963-67 and 1968-72 cumulations, J. W. Edwards, Ann Arbor; 1973-77 cumulation, Rowman and Littlefield, Totowa, New Jersey.
Vols. for < 1979- > compiled and edited by the Catalog Publication Division of the Processing Dept.
Quinquennial cumulations include the quinquennial cumulations of: Music and phonorecords, 1958-1972; Music, books on music, and sound recordings, 1973- ; Motion pictures and film strips, 1958-1972; Films and other materials for projection, 1973-1977 (Vols. for 1979- called: Audiovisual materials, ISSN 0190-9827).
Keywords: Union catalogs -- United States -- Periodicals